Caracterização de genótipos de arroz submetidos aos estresses de frio e profundidade de semeadura - Bevilacqua, Caroline Borges (2013)
Cold stress adversely modifies their physiology, metabolism plant growth and development, as well as, it limits crop productivity. The responses of rice (Oryza sativa L.) subjected to low temperatures are still poorly understood. A better understanding of stress tolerance mechanism in rice plants will help to develop rice germplasm with improved field level tolerance under variable temperature and sowing depth conditions. To characterize rice genotypes with variation in sensitivity to cold, these are the following objectives: to evaluate the applicability of different Stress Indices using seedling lengthas parameter; classify accessions cultivated rice and red rice as Indica or Japonica; compare response to rice cultivars cold-tolerant and cold-sensitive to cold stress according to the dry matter accumulation and possible changes in chlorophyll content; categorize different genotypes with regard to sensitivity to cold and to sowing depth stresses and, analyze the expression of cold-responsive genes, and also genes submergence-responsive. The seeds after seven days at 25°C were exposed at 4°C for 24h and after that, photosynthesis was measured later, the plants were 72h at 25°C (recovery period) to assess the dry mass and chlorophyll. For the other experiments, the seedlings were collected 7 and/or 14 days maintained at 25°C or 18/13°C day/night and different sowing depths (1.5cm, 5cm, 10cm and 15cm), differential gene expression were performed with those seedlings using different genes induced by cold. To evaluated gene expression using different genes induced by cold and anoxia, samples were collected after exposure to 10 ° C for 6, 24 and 96 h at 1.5 cm and 10 cm deep sowing. The results showed that is possible to identify superior genotypes for tolerance to these abiotic stresses based on the Tolerance Index (STI) and Media Geometric (GM) to select genotypes tolerant to cold or sowing depth, using as a parameter the seedling shoot length measurement. Japonica and Indica subspecies respond differently to abiotic stresses, however for some of these stress-responsive genes, these subspecies responded similarly. Furthermore, the analysis at the molecular level of cold tolerance and sowing depth indicated the importance of ABA- dependent and ABA-independent signal transduction pathways in plants under abiotic stress.